Innovation in ELT: Multiliteracies Pedagogy for Enhancing Critical Thinking Skills in the 21st Century - Ermawati Zulikhatin Nuroh; Ahmad Munir; Pratiwi Retnaningdyah; Oikurema Purwati (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
The problem with this research is the lack of skills and thinking skills of humane education in the twenty-first century, especially of critical thinking and problem-solving. It is caused by several factors, one of the main factors is, learning that has not been oriented to the development of the twenty-first-century thinking skills and still only focuses on achieving partial-textual knowledge and not on the integrative-contextual understanding of the knowledge learned. In line with this, it takes an effort to improve the critical thinking skills of Indonesian education. The effort should be initiated by engineering the appropriate education model and on target, one of which is multiliteracies pedagogy. This research was conducted using the literature study discussing multiliteracies pedagogy to enhancing critical thinking skills in the twenty-first century. Literature review refers to a written synthesis of journal articles, books, and other documents that summarizes and critiques the past and current state of information about a topic, organizes the literature into sub-topics, and documents the background for a study. It can be concluded that the implementation of the multiliteracies pedagogy models is one of the alternative learning models that can improve critical thinking and problem-solving students in the university effectively in the areas of study taught compared to the most direct models used in English Language Teaching (ELT). Therefore, it is advisable to implement multiliteracies pedagogy in the practice of learning activities. Also, the application of multiliteracies pedagogy should be supported by the cooperation of all elements, both between teachers, management, and parents. This needs to be done to realize the effectiveness of quality learning, thus giving implications on the growth of potential students.